Activation of the tectonosphere and hydrocarbon deposits - V. V. Gordienko (Геофизический журнал, 2011)
Processes of hydrocarbons generation and transfer in earth's crust are considered. They are conformed to the advection-polymorphous hypothesis. Thermal models of tectonospheres in recent activization zones of the Precambrian platforms and the Alpine geosynclines have been analyzed. Schemes of geological objects and sources of geophysical field anomalies have been plotted. They are in concordance with well-known geological-geophysical data in the regions with oil- and gas-fields.